THYROID ECTOPIA: ANALYSIS OF THE LITERATURE DATA AND CLINICAL OBSERVATIONS - A. Z. Almyashev (Креативная хирургия и онкология, 2017)
Different versions of ectopic  thyroid  gland  are rare in routine  clinical practice  and are associated with a defect of thyroid embryogenesis in its early stages. Symptoms  depend on the location and size of ectopic thyroid function and its morphological structure. Diagnosis is based  on  ray  methods of  investigation. Choice  of  treatment:  hormone suppression, radiofrequency ablation, surgery.